Experimental and simulation study on preheating pulverized coal and air flow by a heat exchanger using thermal oil. (15th May 2021) - Lai, Zhenya; Zhou, Hao; Li, Yuan; Zhang, Pingan; Mao, Rui; Ren, Liming; Zhou, Mingxi
Highlights: A novel technology preheating pulverized coal air flow is proposed. Pilot-scale experiments were carried out to study the preheating performance. The CFD numerical simulations were conducted. The technical feasibility of the preheating technology was verified. The preheating technology can promote the ignition and stabilization of pulverized coal combustion. Abstract: Utility boilers consume a lot of fuel oil during the startup and low-load operation, which leads to the rise of power generation costs and environmental pollution problems. A finned shell-and-tube heat exchanger is proposed to preheat pulverized coal and air flow using thermal oil. Pilot-scale heat exchange tests were carried out to study the effects of the oil temperature, air temperature, air velocity, oil flow rate, coal-air ratio on the preheating performance and resistance properties of the system. Meanwhile, Computational fluid dynamic (CFD) numerical simulations were conducted. The tests verified the technical feasibility of the heat exchanger using thermal oil to preheat the primary air. The proposed preheating process is conducive to environmental protection and energy-saving. The test results show that when the coal-to-air ratio is 0.15, the 190 ℃ of thermal oil can preheat the pulverized coal and air flow from 65.2 ℃ to above 115 ℃. This preheating process will improve the ignition performance of the pulverized coal and air flow, which is favorable for startup and stable operation of the pulverized coal boiler, particularly when the boiler load is low.